Efficacy of Coconut Water as a Seed Priming Agent for Enhancing Germination and Emergence of Rice - Carganilla, Jonabelle; Aquino, Jenny; Dinay-og, Jessica; Cumahling, Glen Joy; Valdez, Manolo (Journal of Interdisciplinary Perspectives, 2025)
Low-cost, eco-friendly seed priming agents are increasingly sought after to improve rice (Oryza sativa L.) germination and establishment, especially for farmers with limited resources. Coconut water contains growth-promoting hormones such as cytokinins and gibberellins, but the optimal concentration and soaking duration for rice seed priming remain unclear. This study evaluated the effectiveness of coconut water at different concentrations and soaking times in enhancing germination, emergence, and early seedling growth. A one-factorial experiment, in a Completely Randomized Design (CRD) with three replications, was conducted under greenhouse conditions, testing four coconut water concentrations (25%, 50%, 75%, and 100%) and two soaking durations (12 and 24 hours), along with distilled water and untreated controls. Germination factors (percent germination, mean germination time, germination uniformity) and emergence and growth traits (percent emergence, shoot length, stem diameter, biomass) were measured. Results showed that priming with 25% coconut water for 12- 24 hours achieved the highest germination rate (97.33%), the fastest mean germination time (38.87 hours), and the most uniform germination. These were statistically similar to priming with distilled water but better than untreated seeds (86.67%). Emergence reached 100% in seeds primed with either 25% coconut water or distilled water, along with significant improvements in shoot length (32.74 cm), stem diameter (5.28 mm), and shoot biomass (fresh weight: 1.60 g; dry weight: 0.61 g). Higher coconut water concentrations (≥50%) did not improve performance and sometimes reduced growth, likely due to osmotic stress. Root biomass was unaffected by the treatments. These findings suggest that 25% coconut water is a practical, affordable, and sustainable alternative to synthetic priming agents. It promotes faster, more uniform germination and stronger early shoot growth without harming seed viability. This method is particularly suitable for smallholder rice farmers looking to improve crop establishment in resource-limited conditions.